SISTEM INFORMASI GEOGRAFIS PEMETAAN BUDIDAYA UDANG PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI NTT - Naibesi, Maria Graciana (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2022)
Shrimp (Caridea) is the main commodity htat is most enjoyed as food, because the meat is savory and very much loved by many people. East Nusa Tenggara Province is one of the provincein indonesia. Indonesia which covers the eastern part of the Nusa Tenggara Islands. East Nusa Tenggara Province has a capital city in kupang city and has 22 districts. East Nusa Tenggara Povince is located in sunda kecil. In 2020, the population of East Nusa Tenggara Province is 5,325,566 people, with a density of 111 people/km². the province of East Nusa Tenggara, the capital city of kupang, is geographically located at 8-12º south latitude and 118-125º east longitude. The problem found at the department of marine affairs and fisheries of east Nusa Tenggara Province is thet the information about the distribution of shrimp around the sea in the Province of east Nusa Tenggara is not sufficient so that a geographic information system is needed that can help the community and fishermen around to find out about the development of GIS- based technology to map shrimp farming at the department of marine affairs and fisheries of East Nusa Tenggara Province. This study aims to produce a GIS- based information system that is expected to assist the department of marine affairs and fisheries in collecting shrimp culture data so that shrimp mapping information is very accurate. The application used in this research is Quantum GIS. With this information system, it is hoped that it will provide a geograihic information system regarding GIS-based shrimp farming in order to provide integrated information and data collection taken by the authors of the department of marine affairs and fisheries of East Nusa Tenggara Province. In addition, to provide convenience, in finding the location pf the shrimp ponds related to finding out information about the services provided. Ktenna used in mapping shrimp in East Nusa Tenggara Province.